Young road users in a district of South India: gender differences in behaviour and perceptions - Uthkarsh, Pallavi Sarji; Kraft, Thomos; Merode, Frits Van (International Journal Of Community Medicine And Public Health, 2020)
Background: Road traffic injuries are the leading cause of death among young people globally, especially in developing countries and burden is more among males compared to females. Human behaviors play a significant role in road traffic Injuries (RTIs), understanding road user behaviors, perception and gender differences in them is very essential to plan strategic road traffic injury prevention programs. The objectives of this study behaviors, risk perception and gender differences in young road users of a district of South India. Methods: This cross-sectional study was undertaken among 2000 young people in the age group of 18-25 years in a district of South India. Results: More than half of the youth reported unsafe behaviors as a road user. Risk behaviors such as playing on roads, using mobile while on road, high speed driving, hanging on to the doors of the bus were reported more in male gender. More than 40% perceived not following traffic safety norms as safe without significant gender differences. Conclusions: Young road users of South Indian district irrespective of gender, do not follow majority of safety norms and they perceived its safe not to follow them.